Idiopathic toe walkers: Do they need surgery? - Alice Bonnefoy-Mazure; Marys Revaz; Camille Leroquais; Geraldo de Coulon; Pierre Lascombes; Stéphane Armand (PLoS ONE, 2025)
Aim The aims of study were: to observe gait parameters evolution for group of patients with surgery and conservative treatment; to compare these parameters for a group of matched patients with surgery and without; to compare these parameters with a group of asymptomatic children. Background Depending of the importance of the equinus in idiopathic toe walking (ITW) patients, conservative or surgical treatment could be proposed. Currently, there is no consensus about the treatment of ITW. Methods ITW patients with surgical or conservative treatment and with two clinical gait analysis (CGA before and after treatment) were selected. Gait parameters have been used as: presence of first ankle rocker, peak ankle power generation, ankle passive dorsiflexion with extended and flexed knee. Paired and Unpaired t-test were used to analyse differences between the 2 CGA, between groups of treatment and with asymptomatic children. Results Sixteen ITW patients were treated surgically with a mean age at baseline of 8.6y and a follow-up time of 2.1y. Thirteen ITW patients were treated conservatively with mean age at baseline of 6.5y and a follow-up time of 3.0y. Only surgery group had a significant improvement in passive ankle dorsiflexion. Both groups significantly improved their parameters. Ten patients in each group were similar in terms of passive ankle dorsiflexion at the first CGA. Passive dorsiflexion and ankle power were significantly greater for the surgery group at the second CGA. Parameters were significantly lower compared to asymptomatic children. Conclusions Regardless of the treatment, the gait quality of the ITW patients improves over time but does not recover the gait of healthy children. Level of evidence This study was a therapeutic retrospective comparative study (level III)